2010
DOI: 10.2519/jospt.2010.3209
|View full text |Cite
|
Sign up to set email alerts
|

The Simple Shoulder Test Is Responsive in Assessing Change Following Shoulder Arthroplasty

Abstract: Shoulder arthroplasty (SA) is an accepted means of pain relief and improving function in patients with advanced joint destruction. 35 Measures of physical impairment and selfreported function are commonly used to assess the outcomes of these procedures. Various self-reporting scales are available to measure the functional outcome of shoulder surgery, but only a few While the responsiveness of the SST has been established for rotator cuff repair, it has not been determined for patients undergoing arthroplasty.t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(37 citation statements)
references
References 35 publications
4
32
0
Order By: Relevance
“…Patients reported the questions of the scales were relevant and clear for shoulder disorders. This finding confirms the acceptability and face validity of the PSST and the POSS in line with the original English and translated versions of the scales (SST: [10,13,[15][16][17][18][19]37]; OSS: [20][21][22][23][24][25][26][27]38]). Responding to all questions of the scales indicates that both the PSST and POSS can accurately evaluate a patient's function and disability.…”
Section: Acceptabilitysupporting
confidence: 84%
See 1 more Smart Citation
“…Patients reported the questions of the scales were relevant and clear for shoulder disorders. This finding confirms the acceptability and face validity of the PSST and the POSS in line with the original English and translated versions of the scales (SST: [10,13,[15][16][17][18][19]37]; OSS: [20][21][22][23][24][25][26][27]38]). Responding to all questions of the scales indicates that both the PSST and POSS can accurately evaluate a patient's function and disability.…”
Section: Acceptabilitysupporting
confidence: 84%
“…The total scores for SST range from 0 (worst or extreme limitations in physical function) to 12 (best or no physical limitation) which can be transformed to a 0 (worst function)-100 (best function) scoring system calculated as: (number of ''yes'' responses/number of completed questions) 9 100 = % ''yes'' responses [12]. The SST is reliable, valid, and responsive [10,13,14]. The SST has been validated in Lithuanian [15], Italian [16], Dutch [17], Portuguese-Brazilian [18], and Spanish [19].…”
Section: Introductionmentioning
confidence: 99%
“…An a priori power analysis suggested that a study group with a minimum of 22 patients who underwent RSA and a matched group of 88 patients (1:4 ratio) who underwent TSA for a diagnosis of GHOA would be necessary to detect a minimum clinically important difference of 12 points on the American Shoulder and Elbow Surgeons (ASES) scoring system and 2 points on the Simple Shoulder Test (SST). 34,42 Variance was estimated to be 18 points on the basis of an analysis of outcomes across all RSAs performed by the senior author (M.A.F.) during the study time frame.…”
Section: Methodsmentioning
confidence: 99%
“…Prior studies generally have used the limited goals criteria of Neer et al [15] or postoperative outcome scores alone without preoperative data, rather than minimum clinically important improvement in a functional outcome score. The Simple Shoulder Test (SST) [11] is a patient-reported outcome score with shown responsiveness and construct validity for shoulder arthritis [17]. A clinically important percentage of maximum possible improvement (%MPI) has been defined as an improvement of 30% of the total possible improvement on the 12-point scale (with higher scores representing better results) [6,12].…”
Section: Introductionmentioning
confidence: 99%